Star Wars Epic Battles - Beecroft, Simon (London ; New York : Dorling Kindersley, 2008)
Describes some of the major battles that took place in the Star Wars universe between the Republic and the Trade Federation, later known as the Empire.
Includes index.
Keywords: Star Wars films -- Miscellanea -- Juvenile literature